Psychological characteristics socialization of adolescents studying in residential care - Deynichenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In article was discussed the problem of children’s socialization in foster home conditions, and the effect of deprivation conditions on the psychological development of adolescents. By an experimental approach was revealed, that the adolescents from the foster home have such measures as rejection of himself as an individual, social isolation, aggressive behavior, anxiety, frustration, lack of communication skills. That promotes deformation of socialisation. The sociotherapy proprosed to perform as effective way of successful adaptation of adolescents to the social conditions.